What you need to know about starting a business - Duncan, Kevin, 1961- (What you need to know., 2011)
Ever wanted to be an entrepreneur? Ever wanted to control what you do, when you do it and stop just making money for someone else? Now is your chance. Starting up a business has never been more exciting. This book explains what you really need to know to make your business a success: How you'll know if you've got a good idea The practicalities of setting up a company How to manage the money How to sell what you do How to make sure you stay soon through it all. This is the book you need to swagger into the Dragon's Den full of confidence. Introduction Chapt.